Safety of biologic and nonbiologic disease-modifying antirheumatic drug therapy in veterans with rheumatoid arthritis and hepatitis B virus infection: a retrospective cohort study - Burton, Mary Jane (Arthritis Res Ther, 2015)
INTRODUCTION: We evaluated the safety of current treatment regimens for patients with RA and HBV in a large US cohort. METHODS: We identified biologic and nonbiologic treatment episodes of RA patients using 1997 to 2011 national data from the US Veterans Health Administration. Eligible episodes had evidence of HBV infection (HBV surface antigen, HBV core antibody, HBV e-antibody and/or HBV DNA) and had a baseline alanine aminotransferase (ALT) <1.5 times the upper limit of laboratory normal within 90 days prior to initiation of a new biologic or nonbiologic DMARD. The main outcome of interest was hepatotoxicity, defined as ALT elevation >100 IU/mL. Results were reported as the cumulative incidence of treatment episodes achieving hepatotoxicity at 3, 6 and 12 months post biologic exposure. RESULTS: Five hundred sixty-six unique RA patients with HBV contributed 959 treatment episodes. Mean age was 62.1 ± 10.3 years; 91.8% were male. Hepatotoxicity was uncommon, with 26 events identified among 959 episodes (2.7%) within 12 months. Hepatotoxicity was comparable between biologic and nonbiologic DMARDs (2.6% vs. 2.8%, P = 0.87). The median time between HBV screening and starting a new RA drug was 504 days (IQR 144, 1,163). Follow-up HBV testing occurred among 14 hepatotoxicity episodes (53.8%) at a median of 202 days (IQR 82, 716) from the date of ALT elevation. A total of 146 (15.2%) treatment episodes received at least one test for HBV DNA at any point in the observation period. CONCLUSIONS: Among US veterans with RA and HBV the risk of hepatotoxicity is low (2.7%), and comparable between biologic and nonbiologic DMARDS (2.8% vs. 2.6%, P = 0.87). HBV testing associated with DMARD initiation or hepatotoxicity was infrequent. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-015-0628-z) contains supplementary material, which is available to authorized users.